New forms of library marketing based on example of word of mouth marketing. The experience of Polish libraries - Wojciechowska, Maja (Qualitative and Quantitative Methods in Libraries, 2017)
The paper presents basic rules of word of mouth marketing. It describes the importance of this tool on the book market, and illustrates the possibilities offered by libraries. It discusses briefly the primary role of the sender's message, the types of messages, channels, customers, and the influence of information on the word of mouth marketing. The paper presents also the results of the research.